In Vivo Imaging of Caenorhabditis elegans Glycans - Laughlin, Scott T. (American Chemical Society, 2009)
[Image: see text] The nematode Caenorhabditis elegans is an excellent model organism for studies of glycan dynamics, a goal that requires tools for imaging glycans in vivo. Here we applied the bioorthogonal chemical reporter technique for the molecular imaging of mucin-type O-glycans in live C. elegans. We treated worms with azidosugar variants of N-acetylglucosamine (GlcNAc), N-acetylgalactosamine (GalNAc), and N-acetylmannosamine (ManNAc), resulting in the metabolic labeling of their cell-surface glycans with azides. Subsequently, the worms were reacted via copper-free click reaction with fluorophore-conjugated difluorinated cyclooctyne (DIFO) reagents. We identified prominent localization of mucins in the pharynx of all four larval stages, in the adult hermaphrodite pharynx, vulva and anus, and in the tail of the adult male. Using a multicolor, time-resolved imaging strategy, we found that the distribution and dynamics of the glycans varied anatomically and with respect to developmental stage.